An implementation science primer for psycho-oncology: translating robust evidence into practice. Issue 3 (December 2019) - Rankin, Nicole M.; Butow, Phyllis N.; Hack, Thomas F.; Shaw, Joanne M.; Shepherd, Heather L.; Ugalde, Anna; Sales, Anne E.
Abstract: Background: It is broadly acknowledged that the next global challenge for psycho-oncology is the implementation of robust evidence-based treatments into routine clinical practice. There is little guidance or texts specific to psycho-oncology to guide researchers and clinicians about implementation science and how to optimally accelerate the translation of evidence into routine practice. This article aims to provide a primer in implementation science for psycho-oncology researchers and clinicians. Methods: We introduce core concepts and principles of implementation science. These include definitions of terms, understanding the quality gap and the need for solid evidence-based interventions. Results: The conceptual models, frameworks, and theories that are used in implementation research are outlined, along with evaluative study designs, implementation strategies, and outcomes. We provide a brief overview of the importance of engaging teams with diverse expertise in research and engaging key stakeholders throughout implementation planning, conduct, and evaluation. The article identifies opportunities to accelerate the implementation of evidence-based psychosocial interventions. Opportunities for greater collaboration across disciplines are highlighted. Examples from psycho-oncology and the broader oncology literature are included to help operationalize concepts. Conclusion: This article describes the fundamental concepts and principles of implementation science for a psycho-oncology audience, to increase the number and quality of implementation studies across the discipline.